PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS IX-2 - Emily Muslimah; Yenita Roza; Susda Heleni (Jurnal Ilmiah Matematika Realistik, 2026)
This investigation was spurred by the poor academic results in mathematics of student due to difficulties in understanding mathematical concepts and the absence of involvement from students in the educational process. To address this issue, the Problem-Based Learning (PBL) model was implemented to improve the learning outcomes of class IX₂ students at Junior High School of YLPI P. Marpoyan Pekanbaru. Engaging 16 students (6 females and 10 males) from the odd semester of the 2025/2026 academic year, this research applied Classroom Action Research (CAR). The study was executed across two distinct cycles, each following a structured sequence of planning, action, observation, and reflection. The learning tools included Learning Objective Flow (ATP), teaching modules, and Student Worksheets (LKPD). The instruments used for data collection included observation sheets for classroom activities and mathematics learning tests. The results demonstrated that the PBL model integration positively affected students' learning outcomes. This was evident from the significant growth in learning mastery, which progressed from 37.5% at baseline to 68.75% and 93.75% in the first and second summative assessments, respectively. Ultimately, the PBL model proves effective in advancing both learning quality and students' mathematical achievement.